Community strengthening and mental health system linking after flooding in two informal human settlements in Peru: a model for small-scale disaster response. (12th March 2018) - Contreras, C.; Aguilar, M.; Eappen, B.; Guzmán, C.; Carrasco, P.; Millones, A. K.; Galea, J. T.
Abstract : Background: Mental health is an important factor in responding to natural disasters. Observations of unmet mental health needs motivated the subsequent development of a community-based mental health intervention following one such disaster affecting Peru in 2017. Methods: Two informal human settlements on the outskirts of Lima were selected for a mental health intervention that included: (1) screening for depression and domestic violence, (2) children's activities to strengthen social and emotional skills and diminish stress, (3) participatory theater activities to support conflict resolution and community resilience, and (4) community health worker (CHW) accompaniment to government health services. Results: A total of 129 people were screened across both conditions, of whom 12/116 (10%) presented with depression and 21/58 (36%) reported domestic violence. 27 unique individuals were identified with at least one problem. Thirteen people (48%) initially accepted CHW accompaniment to government-provided services. Conclusions: This intervention provides a model for a small-scale response to disasters that can effectively and acceptably identify individuals in need of mental health services and link them to a health system that may otherwise remain inaccessible.